Using Whole Genome Sequencing to Trace, Control and Characterize a Hospital Infection of IMP-4-Producing Klebsiella pneumoniae ST2253 in a Neonatal Unit in a Tertiary Hospital, China - Bai, Yuanyuan; Shao, Chunhong; Hao, Yingying; Wang, Yueling; Jin, Yan (Frontiers in Public Health, 2021)
Background The purpose of this study is to use whole genome sequencing (WGS) combined with epidemiological data to track a hospital infection of the carbapenem-resistant Klebsiella pneumoniae (CRKP), which affected 3 neonatal patients in the neonatal intensive care unit (NICU). Methods The minimum inhibitory concentrations for the antimicrobial agents were determined according to the guidelines of the Clinical and Laboratory Standards Institute. Beta-lactamases were investigated using the polymerase chain reaction and DNA sequencing. The transferability of the plasmid was investigated by a conjugation experiment. The clonal relationships were evaluated using multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). WGS and single nucleotide polymorphisms (SNPs) analysis were performed on the CRKP isolates to investigate how the infection might progress. Results Nine CRKP isolates were obtained from the NICU, seven from three patients, one from a duster cloth and one from the hand of a nurse, they all harbored blaIMP-4. Other resistance genes including blaKPC-2, blaIMP-4, blaSHV-1, blaTEM-1, blaCTX-M-15 and blaDHA-1 were also detected. PFGE analysis showed that IMP-4-producing K. pneumoniae were clonally related, and MLST assigned them to a new sequence type 2253. The SNP variations throughout the genome divided the 9 strains into three clades. Clade 1 comprised 7 strains (K1- K2 and K4-K8), whereas clade 2 and 3 consisted of only one strain each: K3 and K9, respectively.The sputum isolate K3 from patient 3 was the most distinct one differing from the other 8 isolates by 239-275 SNPs. Conclusions This is a report of using WGS to track a hospital infecion of IMP-4-producing K. pneumoniae ST2253 among neonates. Nosocomial surveillance systems are needed to limit the spread of the infection caused by these pathogens resulting from the environmental exposure in NICUs.